Rare and Precious Chinese Materia Medica: Pseudobulbus Cremastrae seu Pleiones - Hisayoshi Norimoto; Chiaki Murayama; Feng Zhao; Hong-Yan Wei (Wolters Kluwer Health/LWW, 2021)
Shan Ci Gu (山慈菇 Pseudobulbus Cremastrae seu Pleiones), a rare and precious traditional Chinese medicine, has attracted attention for the treatment of various cancers and bacterial infections. According to the Pharmacopoeia of the People's Republic of China, Pseudobulbus Cremastrae seu Pleionesis sourced from the pseudobulbs of three plants in the Orchidaceae family: Cremastra appendiculata (D. Don) Makino, Pleione bulbocodioides (Franch.) Rolfe, and Pleione yunnanensis Rolfe. Extracts from Pseudobulbus Cremastrae seu Pleiones are used for the treatment of tumors, burns, and frostbite. The aims of this review are to provide information on the historical and herbological origins of Pseudobulbus Cremastrae seu Pleiones, to summarize research conducted on its phytochemical and biological activities over the last twenty years, and to detail planting efforts.